Control of a four-wheel ROV on a circular surface - Yan, Qucheng (2017)
The demand for water resources is expected to double by 2060, with the expected growth of population and industry in Singapore. DTSS – Deep Tunnel Sewage System inspection robot plays an important part to ensure the tunnel health and water transportation. The current DTSS robotic platform developed by NTU Robotic Research Center selected skid steering system for its simple design and effective control. Despite many studies were done on skid steering control and performance, most studies only focus on the situations where skid steering on flat grounds. However, DTSS robotic platform is meant for steering on the circular tunnel. Hence, the objectives of this report are to provide a new perspective to approach skid steering on a circular surface. The scope of this report considers the review on the popular steering system, experiments on the skid steering based on the existing DTSS robotic platform and development of a SolidWorks simulation tool for study the steering system. Three robot models were constructed and SolidWorks motion analysis was set up for steering simulation on a D = 3m circular surface. The simulation focus on two categories: pivot turning and maneuverability test from off-center position. Simulation results were cross compared among different models and It shows that the steering performance is closely related to the robot dimensions. Experiments on the current DTSS robotic platform and another robotic prototype were carried out. The results obtained from the actual steering tests shows that the force interaction behavior between the robotic platform and the circular surface. Based on the experiment results, the SolidWorks simulation tool was justified, and further improvements were suggested.